Managing psychiatric issues in elite athletes - Glick, I. D.; Stillman, M. A.; Reardon, C. L.; Ritvo, E. C. (The Journal of Clinical Psychatry, 2012)
Objective: Providing psychiatric consultation to elite athletes presents unique and complex issues. These patients present with multifaceted medical, psychological, and performance concerns. We provide the first report of professional and ethical quandaries that arise in treating elite athletes and ways to address them.